Environmental Information Services and Development - Rogers, David (Washington, DC: World Bank, 2012)
The paper discusses the elements that need to be addressed or implemented to make effective use of climate information for development. Key organization changes are needed. Integrating climate change into development policy is demanding requiring input from many different sectors, which are individually and collectively affected by environmental change. Much more effective partnering is needed across all of these sectors. This does not require new institutions, but organizational change that emphasizes collective responsibility for the problem. In particular, it requires the ability to work across all of civil society, both governmental and nongovernmental, and the ability to obtain commitments from any and all of the participating institutions. The involvement of the private sector is essential because they can actively contribute to the collection of much needed climate data and information.